THE USE Of TRADITIONAL MEDICINE BY WOMEN WITH HYPERTENSION IN WEDI - AS, Indarto; Ambarwanto, Sigit Tri; Kirwanto, Agus; Siku, Sherlyani Maria Natalia (Jurnal Jamu Kusuma, 2024)
One of the non-communicable diseases that becomes a major risk factor for cardiovascular disease is hypertension. The prevalence of women with hypertension in Wedi district is 38.9%. This study aims to explore how women who have hypertension use traditional medicine in Wedi District. This type of research is qualitative with a phenomenological approach. The results of this study include: The definition of high blood pressure disorder is when a person has a blood pressure of more than 140 or more than the normal blood pressure of 120, but when checked repeatedly, the blood pressure is not stable. In addition, direct causes of hypertension such as disease, age, and gender. Meanwhile, indirect causes such as food and drinks, body conditions, and psychological disorders. Meanwhile, signs and symptoms of hypertension include physical disorders and psychological disorders. Hypertension may cause organ malfunction, activity disruption, and psychological disorders. Thus, the first aid taken is varied, such as seeking treatment at health care facilities, seeking treatment at health workers, seeking treatment at traditional health workers (Nakestrad), and self-medicating. Furthermore, traditional skills-based therapy can be done, including dry cupping, walking on gravel, self-soothing therapy, etc. Meanwhile, jamu can also be used to maintain blood pressure, such as jamu beras kencur, jamu hipertensi saintifik, etc. They also use some medicinal plants, including kenikir leaves, papaya leaves, etc. It can be concluded that not all women know about hypertension, and their efforts to maintain their blood pressure greatly vary both conventionally, traditional medicine (skills, herbs, and medicinal plants), and self-medicate.